Gestão pública associada : um estudo sobre o Consórcio Público do Agreste Central Sergipano - Silva, Elvis Lima Moura da (2016)
The Política Nacional de Resíduos Sólidos (National Policy of Solid Waste - PNRS) has established as one of its goals the ending of all dumping grounds all over the country until 2014. In 2016, 75% of the Sergipe‘s municipalities waste are intended to environmentally inappropriate areas. Among the various instruments proposed by PNRS to solve this issue by the municipalities, especially the ones that have small and medium-size, it shows the formation of consortiums for joint management of municipal solid waste, given the lack of human and finantial resources to the expense coverage, especially with the final destination, in addition to the cost reduction potential with increasing administered scale. This technical report investigated how is structured the Consórcio Público do Agreste Central Sergipano (Public Consortium of the Central Sergipean Agreste), created to manage the sector of twenty municipalities in the region. He attempted to present the regional‘s panorama of the solid waste sector and expose the balance of management and governance in the intermunicipal authority under three dimensions: political, administrative, budgetary and financial-control. As for management, the consortium presents with adequate structure to the current legislation, but still limited as to institutional planning and operation of important internal organs such as the Board of Adjustment. The governance structure was insufficient, lacking prioritization, especially regarding the institutionalization of social control and participation, through the operation of bodies such as the Ombudsman, Internal Control and adjustments of the tools of transparency of actions and access to information. The report ends with the emphasis on the viability of the consortium of solid waste management in the region and a proposal for action aimed at the improvement of the Consortium management and governance structures.